Arctic shipping 2013–2022: the traffic has grown, with big variation between regions, seasons and ship types - Sander, Gunnar; Mikkelsen, Eirik (Polar research, 2025)
This article analyses decadal changes in Arctic ship traffic from 2013 to 2022, using data from the Arctic Ship Traffic Data system (ASTD). Shipping in waters affected by sea ice has grown, but how much depends on geographical definitions. The Polar Code area had an average annual growth of 8.7%, mainly due to more traffic in the Barents Sea, where most Arctic ship traffic occurs. Where analysts set the southern boundary of the Barents Sea significantly influences the statistics, for example, to what extent fishing vessels dominate Arctic shipping. Reports on Arctic shipping should consider the significant intra-Arctic variations in activity levels, growth rates and traffic composition. The Kara Sea experienced the biggest annual growth rate—14% on average—because of petroleum projects that have introduced big oil and gas tankers. In contrast, there is minimal activity and growth in the Large Marine Ecosystems of the Northern Canadian Archipelago and the Central Arctic Ocean. Even though the winter traffic has grown in the Barents Sea, the Kara Sea and Baffin Bay, the activities there remain distinctly seasonal. In other seas, ships almost vanish in winter. Transit shipping over the Arctic is still insignificant in a global context. The standard reports in the ASTD are important for understanding Arctic shipping and should be improved. In particular, the Polar Code area needs to be subdivided to enable consistent reporting on overall pan-Arctic and intra-Arctic developments. Definitions for transit traffic should also be agreed upon and opportunities for automatic reporting accordingly investigated.